Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

a = –3
b= –5

(a –b).(b – a)³ ?


Sagot :

The answer you are looking for is -16.

Solution/Explanation:

Writing out the expression first

(a-b)(b-a)³

Substituting the given values of the variables

[(-3)-(-5)][(-5)-(-3)]³

Simplifying

(-3)-(-5)=-3+5=2

(-5)-(-3)=-5+3=-2

(2)(-2)³

(-2)³=-8

You will get (2)(-8)

(2)(-8)=-16

You will get -16.

So, therefore, the final answer to this problem is -16.

Hope this helped answer your question for you. Good day to you.